2020
DOI: 10.4103/jfmpc.jfmpc_630_20
|View full text |Cite
|
Sign up to set email alerts
|

Etiological spectrum of infectious keratitis in the era of MALDI-TOF-MS at a tertiary care hospital

Abstract: Background: Infectious Keratitis (Ik) Is A Potential Vision-Threatening Ocular Infection Caused By A Variety Of Microorganisms. Aim: To Explore Risk Factors And Etiological Agents Associated With Ik. Design: A Prospective Cross-Sectional Study In Which Corneal Scrapings From 120 Suspected Cases Were Evaluated At A Tertiary Health Care Institute From January To December 2019. Methods: Scrapings Were Subjected To Dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
(11 reference statements)
0
7
0
1
Order By: Relevance
“…Earlier used only in the diagnosis of bacterial organisms, it has now emerged as a tool to identify isolates of fungi, particularly yeasts, and also a few genera of filamentous fungi, including Aspergillus, Penicillium, Fusarium, and Mucorales [49]. A recent study from a tertiary centre [50] in India found that MALDI-TOF MS used to specifically identify the aetiological spectrum of infective keratitis was able to accurately identify in 51% of cases (100% of culture positive), except 2% of polymicrobial growths. These newer modalities can help identify the exact species involved in the infection which in turn helps to commence appropriate treatment and pave the way for appropriate antifungal susceptibility testing [51].…”
Section: Molecular Diagnostic Methodsmentioning
confidence: 99%
“…Earlier used only in the diagnosis of bacterial organisms, it has now emerged as a tool to identify isolates of fungi, particularly yeasts, and also a few genera of filamentous fungi, including Aspergillus, Penicillium, Fusarium, and Mucorales [49]. A recent study from a tertiary centre [50] in India found that MALDI-TOF MS used to specifically identify the aetiological spectrum of infective keratitis was able to accurately identify in 51% of cases (100% of culture positive), except 2% of polymicrobial growths. These newer modalities can help identify the exact species involved in the infection which in turn helps to commence appropriate treatment and pave the way for appropriate antifungal susceptibility testing [51].…”
Section: Molecular Diagnostic Methodsmentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-ToF MS) has emerged as a breakthrough technique and has been successfully applied in recent years in the field of clinical microbiology for the identification of microorganisms. MALDI-ToF MS Z proves to be a valuable method for quickly diagnosing fungal keratitis, especially for cases involving rare or uncommon fungi [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Advanced Molecular Techniquesmentioning
confidence: 99%
“…[23,28]. Метод характеризуется высокой диагностической эффективностью, экономической целесообразностью в рутинной практике, быстротой получения результатов идентификации и простотой методологии выполнения исследований [29,30]. Применение ПЦР-методов для идентификации возбудителей БК не рекомендуется, так как результаты могут иметь низкую клиническую значимость.…”
Section: микробиологическая диагностика бк с определением антибиотико...unclassified